'Siento que el inglés esta tumbando mi español': A transfronteriza child's embodied critical language awareness. Issue 7 (9th August 2022) - Nuñez, Idalia
ABSTRACT: For many minoritized communities, sustaining or at least holding on to their home language and cultural identity has been a constant uphill battle. Nevertheless, Latina/o/x who speak Spanish, for example, have demonstrated to be linguistically and culturally resilient against hegemonic societal, institutional, political, and monolithic national ideologies. This article explores a single case study of a Latina transfronteriza child's embodied critical language awareness. Merging Critical Language Awareness and Chicana Feminist Theory, the findings demonstrate how a Latina child makes sense of linguistic hierarchies, language loss, and how she challenges deficit perspectives imposed on her home language by relying on her senses and feelings. The article concludes by offering ways to understand and support critical language awareness with Latina/o/x students that stems from knowledge rooted in the brown body and their lived experience.